Relationship between postoperative integrity of subscapularis tendon and functional outcome in reverse shoulder arthroplasty - Collin, Philippe; Rol, Morgane; Muniandy, Moganadass; Gain, Solenn; Lädermann, Alexandre; Ode, Gabriella (Journal of shoulder and elbow surgery, 2022)
The role of the subscapularis in reverse shoulder arthroplasty (RSA) remains controversial. Studies have shown that subscapularis repair has no significant influence on the functional outcomes of patients. However, few studies have assessed the postoperative integrity of the subscapularis tendon after RSA. The aims of this study were to investigate the postoperative healing of the subscapularis after RSA via ultrasound and to evaluate the relationship between tendon integrity and functional outcomes. We hypothesized that subjects with a healed subscapularis after RSA would have higher Constant scores and better internal rotation (IR) than those without a healed subscapularis. This was a retrospective review of all patients who underwent primary RSA with subscapularis tenotomy repair performed by a single surgeon with a minimum 2-year follow-up period. The inclusion criteria were (1) primary RSA and (2) complete intraoperative repair of the subscapularis tenotomy if the tendon was amenable to repair. The total Constant score and active and passive range of motion were measured preoperatively and at every postoperative visit. IR was further subcategorized into 3 functional types (type I, buttock or sacrum; type II, lumbar region; and type III, T12 or higher). The integrity of the subscapularis on ultrasound at 2 years was reported using the Sugaya classification. The correlation between subscapularis integrity and functional outcomes including functional IR was evaluated. A total of 86 patients (mean age, 73 ± 7.4 years; age range, 50-89 years) were evaluated. The mean postoperative Constant score for all patients significantly improved from 38 points to 72 points (P < .001) at last follow-up (mean, 3.3 years). There was significant improvement in all Constant score functional subscales and in terms of range of motion. The rate of sonographic healing of the subscapularis was 52.6%. There was no difference in Constant scores between “intact” and “failed” tendon repairs; however, intact tendons demonstrated significantly better IR with no difference in external rotation (P < .01). The healing rate of the subscapularis following RSA was only 52.6%. IR function in patients with an intact subscapularis at 2 years after RSA was significantly better than in patients with failed or absent tendon repairs. Primary repair of reparable subscapularis tendons during RSA should be strongly considered.